Heart Rate Variability as a Prognostic Tool for Palliative Patient : A Literature Review - Charlex, Harold Jefferson Matthew; Ardani, Yanuar; Shatri, Hamzah (International Journal of Cell and Biomedical Science, 2023)
Introduction: Heart rate variability (HRV) is the fluctuation in the interval between two heartbeats. Decreased HRV indicates less flexibility of the autonomic nervous system (ANS) to physiological changes and is associated with poorer disease progression and mortality in several diseases. We reviewed conditions where HRV can be utilized as a predictive tool for palliative patients. Methods: We performed a comprehensive search in PubMed, ScienceDirect, and Google Scholar to find articles related to HRV and prognosis for cancer-related disorders, cardiovascular disease, and sepsis. 41 relevant articles were selected and reviewed. Results: ANS changes due to chronic cancer pain and metastastic bone cancer can be detected by HRV analysis and increased vagal activity is related with longer survival on advanced cancer patients. Lower HF is a risk factor for shorter life expectancy of metastatic or recurrent breast cancer. SDNN and RMSSD reduction correlates with poorer survival in NSCLC and metastatic brain cancer. Increased risk of stroke was observed in patients with lower RMSSD and SDNN. Reductions of both scores and LF were associated with two times increased risk of myocardial infarction and higher mortality one year after stroke. A decrease in HRV is related to mortality but is not specific to cardiovascular disease. SDNN and HF are HRV parameters that are most consistently correlated with sepsis and can predict mortality within 30 days of hospitalization. Conclusion: HRV analysis helps in assessing the prognosis of diseases. Typically, reduced HRV is linked to worse outcomes and increased mortality rates in conditions such as cancer, cardiovascular disease, and sepsis.